If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -3z = 8z + -7 + -1z Combine like terms: z + -3z = -2z -2z = 8z + -7 + -1z Reorder the terms: -2z = -7 + 8z + -1z Combine like terms: 8z + -1z = 7z -2z = -7 + 7z Solving -2z = -7 + 7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7z' to each side of the equation. -2z + -7z = -7 + 7z + -7z Combine like terms: -2z + -7z = -9z -9z = -7 + 7z + -7z Combine like terms: 7z + -7z = 0 -9z = -7 + 0 -9z = -7 Divide each side by '-9'. z = 0.7777777778 Simplifying z = 0.7777777778
| x=8pi-pi | | 5(x+2)=4x-8 | | 5(2n+12)=4n | | 150n-50=n+325 | | 2(-5x+5)=-4x+4 | | [5a^2-20a+20]+[3a+3]=25 | | -84=2(6+8a) | | x+3=(x-3)(x-3) | | 3a-45b*j=2 | | 5x+30=11x+48 | | w+(3+w)=25 | | z-3z=8z-7-2 | | 150n-50=100+325 | | 7x^2+12=25x | | -67+6x=-6(-x+7)-4 | | 4x^2-6x=4x^2-3x-27 | | 7x+10=6x+3 | | -9y^2-6y^2+y^2= | | 7(4y-6)=14 | | 4x-3(0)=17 | | -120x=-60 | | -6g=-30 | | 9=X*44 | | -5(4t-4)+6t=8t-9 | | c+(5+c)=33 | | 8-4(2+l)= | | q-21=-7 | | 0=4(0)+7 | | -2(1-4x)+2x=-82 | | 6y+6-5=7 | | 2/5=3/4+y | | -7/3*-11/3=9 |